„Zjednoczona w różnorodności” – wyzwanie dla europejskiej tożsamości prawnej na przykładzie różnorodności językowej - Doczekalska, Agnieszka (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The paper aims at investigating how the European Union, which bases European identity on the motto ‘united in diversity’ deals with the linguistic diversity of Europe. The paper focuses on how the EU developed its language system, especially: how languages, in which EU law is drafted, are chosen; how the concept of EU official and working languages is understood; what is the main challenge of EU legal drafting as far as languages are concerned.